Sacubitril/valsartan ameliorates doxorubicin-induced cardiomyocyte toxicity through inhibiting oxidative stress in rats. (14th October 2021) - Miyoshi, T; Nakamura, K; Amioka, N; Yonezawa, T; Kondo, M; Saito, Y; Yoshida, M; Akagi, S; Ito, H
Abstract: Background: Doxorubicin (DOX)-based chemotherapy induces cardiotoxicity, which is considered the main limitation of its clinical application. Purpose: The present study investigated the potential protective effect of sacubitril/valsartan, an angiotensin receptor–neprilysin inhibitor, against DOX-induced cardiotoxicity in rats and H9c2 cells, and whether the underlying mechanism for any such protection involves its antioxidant activity. Methods: Male Sprague-Dawley rats were randomly divided into four groups: DOX (1.5 mg/kg/day intraperitoneally for 10 days), DOX+valsartan (31 mg/kg/day by gavage from day 1 to day 18), DOX+sacubitril/valsartan (68 mg/kg/day by gavage from day 1 to day 18), and control (saline intraperitoneally for 10 days). There were 15 rats in each group. At the end of the treatment period, samples were collected and analysed. Cardiac function, tissue morphology, and reactive oxygen species (ROS) were evaluated in rats. Serum levels of Malondialdehyde (MDA) and cardiac troponin T were also measured. Mitochondrial ROS production and cell viability were evaluated in H9c2 cells. Results: DOX-induced cardiac dysfunction was not prevented by valsartan and sacubitril/valsartan in this model. However, the serum level of cardiac troponin T on day 18 was increased in the DOX group (0.046±0.006 ng/mL, p<0.01 vs. control) and significantly reduced in the DOX+sacubitril/valsartan group (0.039±0.007 ng/mL, p=0.03 vs. DOX), but not in the DOX+valsartan group (0.046±0.005 ng/mL, p=1.00 vs. DOX). Regarding the effect of sacubitril/valsartan on fibrosis in rat myocardium, Masson's trichrome staining showed increased intestinal fibrosis in the DOX group compared to that in the control group (1.35±0.07% and 0.49±0.04%, p<0.01) and significantly decreased intestinal fibrosis in the DOX+sacubitril/valsartan group (1.08±0.08%), but not in the DOX+ valsartan group (1.15±0.05%) compared to that in the DOX group (p=0.01 and p=0.15, respectively). The fluorescence intensity of dihydroethidium as a measure of ROD production in left ventricle, which was increased in the DOX group (1.56±0.07), was significantly reduced in the DOX+sacubitril/valsartan group (1.44±0.05, p=0.03), but not in the DOX+valsartan group (1.29±0.06, p=1.00). On day 11, the serum MDA level, which was increased in the DOX group, was significantly reduced in the DOX+ sacubitril/valsartan group (p=0.02), but not in the DOX+ valsartan group (p=0.75). In H9c2 cells, sacubitril/valsartan reduced DOX-induced mitochondrial ROS generation by 25%, which was more marked than valsartan-induced ROS generation (p<0.01 and p=0.01, respectively). Sacubitril/valsartan improved cell viability more markedly than valsartan. Thus, DOX-induced cytotoxicity in H9c2 cells was improved by sacubitril/valsartan, but not valsartan. Conclusions: Sacubitril/valsartan protected rat hearts from DOX-induced cardiotoxicity in vivo and in vitro by decreasing oxidative stress. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This work was supported by Novartis Pharma K.K.